ΣΥΝΕΔΡΙΑΣΗ Δ.Σ. 21-10-2019 (ΔΗΜΟΣ ΗΡΑΚΛΕΙΟΥ, 2019)
: ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ ΠΑΛΟΥ